THE ROLE OF COST REDUCTION AND INVENTORY OPTIMIZATION ON THE PARTNERSHIP IN PURCHASING AND LOGISTICS, AN EMPIRICAL STUDY OF FOOD AND BEVERAGE COMPANIES FROM INDONESIA - Sutrisno, Timotius F. C. W.; Kaihatu, Thomas Stefanus (Jurnal Aplikasi Manajemen, 2022)
Supply chain management is of primary importance in industries operating in an archipelago country like Indonesia. This study aimed to determine the effect of cost reduction and inventory optimization on the partnership in purchasing and logistics on purchasing and logistic performance. This study focuses on food and beverage manufacturing companies in Indonesia. This research uses quantitative methods and descriptive research types. The population in this study is managers of manufacturing companies in Indonesia. The questionnaires obtained were 74 respondents, then respondents who came from manufacturing companies were 50 respondents who met the research criteria. This study indicates several findings: cost reduction and inventory optimization affect the partnership in purchasing and logistics but do not affect purchasing and logistics performance. Furthermore, partnership in purchasing and logistics affects purchasing and logistic performance. The results show that the partnership strategy is essential for manufacturing companies, especially food and beverages because cost reduction and inventory optimization need to involve several companies with more resources to increase purchasing and logistic performance.